Surgical treatment of anterior iliac spines fractures: our experience - Pogliacomi, F.; Calderazzi, F.; Paterlini, M.; Ceccarelli, F. (Acta Biomedica Atenei Parmensis, 2014)
Introduction: Iliac spines fractures represent 4% of all pelvic ring fractures and affect more frequently young people with open growth physis. These lesions are usually the consequence of an indirect avulsion trauma due to a sudden and forceful contraction of the muscles that take their origin on these structures. The treatment can be conservative or surgical according to the size and the amount of the dislocation of the fragment. The aim of this study is to evaluate the outcomes of surgical approach of these fractures. Materials and methods: Between 2002 and 2010, 9 patients with fractures of anterior iliac spines were surgically treated. All patients, after an average follow up of 48 months, were evaluated clinically with the Non-arthritic Hip Score (NAHS) and radiographically in order to detect their consolidation. Complications related to the fracture and its treatment were analyzed. Time between trauma and return to sport performance (RSP) was recorded. Results: Mean NAHS was 98 points and RSP averaged 82 days. In 2 cases a transient meralgia paresthetica was observed. In 2 other cases follow-up radiographs showed asymptomatic hyperostosis around the iliac spines. Conclusion: The treatment of iliac spines fractures is mainly conservative. When fragment size is bigger than 2 cm and is dislocated of more than 2 cm surgical treatment is indicated. We recommend a fixation with metallic screws in order to obtain a more stable fixation and an earlier recovery especially in high demanding patients.